Brilhando no palco: a importância do adereço na composição cênica do bailarino sob o olhar de uma bailarina aderecista - PEREIRA, Kate Karolina de Paiva (2018)
This work aims to understand by analyzing the importance of prop in the scenic composition of the dancer, from my experience as a dancer and prop man. During the research will be described the making of scenic props developed by the team and Pereira family to which I belong , especially in the process in which it occurs, drawing a parallel in the importance of understanding this process , where traffic between being a dancer and be prop man , starting from the need to understand this relationship. In this context my research is participatory nature, because it is a direct relationship that I have with my object . Bring concepts Jocimar Daolio author when referring to body culture which deals with the transmission of knowledge and practices from one person to another , dialogue with Patrice Pavis , as I refer to scenic props because it deals with the classification of objects and props and identifies the stage.